Accumulation of coumaric acid is a key factor in tobacco continuous cropping obstacles - Jia, Meng; Wang, Xingsong; Zhu, Xuanquan; Du, Yu; Zhou, Peng; Wang, Ge; Wang, Na; Bai, Yuxiang (Frontiers in Plant Science, 2024)
Introduction Phenolic acids are believed to play a significant role in tobacco continuous cropping obstacles, but the strength and potential mechanisms of different phenolic acids remain unclear. Methods This study evaluated the allelopathic effects of six phenolic acids that exhibited cumulative effects in our previous research. Different concentrations of phenolic acids with the strongest allelopathic effects were added to potting soil to explore their impacts on tobacco growth and physiological characteristics, as well as on soil chemical properties and microbial community structure. Results The results showed that coumaric acid exhibited the strongest direct allelopathic effect. Exogenous coumaric acid significantly reduced soil pH and shifted the soil microbial community from bacteria-dominated to fungi-dominated. Simultaneously, the abundance of bacteria related to nutrient utilization (e.g., Flavisolibacter, Methylobacterium) and fungi related to disease resistance (e.g., Fusicolla, Clonostachys) gradually decreased, along with a reduction in soil catalase, urease, invertase, and acid phosphatase activities. Leaf MDA levels increased continuously with higher concentrations of coumaric acid, while the root resistance hormone (jasmonic acid and the jasmonate-isoleucine complex) levels show the opposite trend. Discussion Coumaric acid may inhibit tobacco growth by influencing the physiological processes in tobacco plants directly and the broader soil microecological balance indirectly. This study provides theoretical guidance for precise mitigation of continuous cropping obstacles in future tobacco cultivation.